2000 days of SMOS at the Barcelona Expert Centre: a tribute to the work of Jordi Font - Turiel, Antonio; Piles, María; González Gambau, Verónica; Ballabrera-Poy, Joaquim; Gabarró, Carolina; Martínez, Justino; Olmedo, Estrella; Portabella, Marcos; Pérez, Fernando; Solé, Jordi (Scientia Marina, 2016)
Special volume: Planet Ocean. Scientia Marina 80(Suppl.1) 2016.-- 21 pages, 18 figures, 1 table [EN] Soil Moisture and Ocean Salinity (SMOS) is the first satellite mission capable of measuring sea surface salinity and soil moisture from space. Its novel instrument (the L-band radiometer MIRAS) has required the development of new algorithms to process SMOS data, a challenging task due to many processing issues and the difficulties inherent in a new technology. In the wake of SMOS, a new community of users has grown, requesting new products and applications, and extending the interest in this novel brand of satellite services. This paper reviews the role played by the Barcelona Expert Centre under the direction of Jordi Font, SMOS co-principal investigator. The main scientific activities and achievements and the future directions are discussed, highlighting the importance of the oceanographic applications of the mission [ES] SMOS es la primera misión capaz de medir la salinidad superficial del mar y la humedad del suelo desde el espacio. La novedad del instrumento que SMOS lleva a bordo (MIRAS, un radiómetro interferométrico en dos dimensiones que trabaja en banda L) ha implicado el desarrollo de nuevos algoritmos para el procesado de los datos obtenidos. Esto ha supuesto todo un reto, no sólo tecnológico sino también científico, puesto que ha sido necesario abordar diferentes cuestiones inherentes al uso de una nueva tecnología. A raíz del lanzamiento de SMOS, ha surgido una nueva comunidad de usuarios con la correspondiente demanda de nuevos productos y aplicaciones, y un interés creciente en este tipo de nuevos servicios satelitales. En este artículo, se detallan las funciones desempeñadas por el BEC (Barcelona Expert Centre) en la misión SMOS, bajo la dirección de Jordi Font, investigador principal de la parte de salinidad de la misión. Asimismo, también quedan reflejadas las principales actividades de investigación llevadas a cabo en este centro, los logros conseguidos y las futuras líneas de trabajo, ...